STUDI KOMPARASI PERSEPSI SISWA PADA IMPLEMENTASI ICE BREAKING DALAM PEMBELAJARAN BAHASA INDONESIA KELAS I DAN KELAS V - Shintya Nur Azizah; Rizka Nur Oktaviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to compare students' perceptions of the implementation of ice breaking in Indonesian language learning in class I and class V. This type of research uses a comparative study. Meanwhile, the research method applied is a quantitative research method. This research used test research instruments, questionnaires, observations and interviews. Data were analyzed using SPSS version 22 software, by applying hypothesis testing via the Mann-Whitney test. The results of the descriptive analysis show that from students' perceptions the data obtained is that the average perception value for class I is 39.35 and for class V the average value is 21.47. The results of the statistical analysis of the Mann Whitney test for student perception showed that the significance value was 0.000, less than 0.05. For this reason, the decision from statistical analysis is that H0 is rejected and H1 is accepted. The results of this research can be concluded that there is a significant difference between the perceptions of students in class I and class V regarding the implementation of ice breaking in Indonesian language learning.